Tp53 Mutation Inhibits Ubiquitination and Degradation of WISP1 via Down-Regulation of Siah1 in Pancreatic Carcinogenesis - Wu, Wei; Liu, Xu; Wei, Lumin; Li, Tong; Zang, Yi; Qian, Yuting; Bai, Tingting; Li, Juanjuan; Xie, Mingping; Zhu, Ying; Wang, Qi; Wang, Lifu (Frontiers in Pharmacology, 2018)
Wnt1 inducible signaling pathway protein-1 (WISP1) may play an important role in promoting carcinogenesis. However, the biological function and underlying mechanism of WISP1 in pancreatic carcinogenesis still remains enigmatic. In this study, immunochemistry staining showed that protein levels of WISP1 were more significantly upregulated in pancreatic ductal adenocarcinoma (PDAC) tissues with Tp53 mutation than in PDAC tissues with Tp53 wild-type. In addition, a significant correlation was observed between increased malignant phenotype of tumors from well-differentiated adenocarcinoma tissues to moderately- or poorly-differentiated adenocarcinoma tissues shifting from cytoplasmic expression to nuclear accumulation of WISP1. Interestingly, WISP1 expression was correlated with the poor prognosis in PDAC patients with Tp53 mutation. Also, the biological function analysis showed that WISP1 may act as a potential oncogene in PDAC cells. In addition, immunofluorescence analysis showed that Tp53 mutation promoted WISP1 expression in PanIN and PDAC cells, while Siah E3 Ubiquitin Protein Ligase 1 (Siah1) inhibited WISP1 expression in PDAC cells. Moreover, through immunoprecipitation, immunoblotting analysis, in vitro binding assay, and ubiquitination assay, we found that Tp53 mutation inhibited ubiquitination and degradation of Siah1-dependent WISP1. Therefore, Tp53 mutation-Siah1-WISP1 is a new signaling pathway, playing an important role in pancreatic carcinogenesis.